Acquisition of a new language: an enriched case study documents language growth without external input in a young Korean child’s acquisition of English - Lust, Barbara; Flynn, Suzanne; Kim, Ahyoung Alicia (Frontiers in Human Neuroscience, 2024)
This paper explores a case of suspension of data input during the acquisition of a second language by a young Korean child acquiring English in an English only nursery school in the US. Data suspension occurred naturally when the child returned to Korea for a summer where only Korean was spoken. Systematic investigations using an enriched case study methodology which assessed the nature of the child’s English target language acquisition both before and after the Korean Summer revealed significant advance in his English after the Korean Summer despite the absence of English input during this time. Several hypotheses regarding the nature and explanation of this advance are tested. It is argued that significant internal linguistic integration leading to systematization of linguistic knowledge occurred in the absence of synchronous language data input, demonstrating the significance of internal computational processes over and above language data input in the language acquisition process. Results have implications for understanding the fundamental nature of language acquisition.